2015
DOI: 10.2967/jnumed.115.165613
|View full text |Cite
|
Sign up to set email alerts
|

Use of PERCIST for Prediction of Progression-Free and Overall Survival After Radioembolization for Liver Metastases from Pancreatic Cancer

Abstract: We evaluated the prognostic accuracy of established PET response criteria in patients with liver metastases from pancreatic cancer after treatment with 90 Y microspheres. Methods: Seventeen patients underwent 18 F-FDG PET/CT before and 3 mo after radioembolization for liver metastases from pancreatic cancer. Overall survival, progression-free survival, and time to intrahepatic progression were among other factors correlated with metabolic response as revealed by PERCIST 1.0-defined declining SUV peak and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
(53 reference statements)
1
12
0
Order By: Relevance
“…Firstly, we used the single-lesion method according to Wahl et al [29], which was shown to be superior to the five-lesion method [22,30]. Secondly, in accordance to Fendler et al, we used peak standardized uptake value corrected for body weight (SUV peak ) instead of lean body mass corrected SUV (SUL peak) as proposed by PERCIST 1.0, because the main objective is the percentage change of SUV from baseline to follow-up imaging and should therefore not be a significant confounder [31]. Riedl et al could also show that response classification was unchanged when SUV max was used instead of SUL peak in patients with metastatic breast cancer [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we used the single-lesion method according to Wahl et al [29], which was shown to be superior to the five-lesion method [22,30]. Secondly, in accordance to Fendler et al, we used peak standardized uptake value corrected for body weight (SUV peak ) instead of lean body mass corrected SUV (SUL peak) as proposed by PERCIST 1.0, because the main objective is the percentage change of SUV from baseline to follow-up imaging and should therefore not be a significant confounder [31]. Riedl et al could also show that response classification was unchanged when SUV max was used instead of SUL peak in patients with metastatic breast cancer [22].…”
Section: Discussionmentioning
confidence: 99%
“…To assess treatment response by mPERCIST change in peak standardized uptake value (SUV peak ) was measured in the tumor region with the highest radiotracer uptake, which describes the average SUV computed in a fixed 1-mL sphere recommended by PERCIST instead of the widely used single-pixel maximum standardized uptake value (SUV max ) to avoid noise errors [18,29]. In a slight modification to the PERCIST 1.0 criteria, the quantitative PET-parameter was adjusted to body weight (SUV peak in g/mL) rather than the body surface area (SUL peak ), as previously described by Fendler et al for the single most active lesion in the patient at baseline, 3 month and 6 month follow-up [31]. A 1 mL spherical VOI was placed at the focus of the single active lesion and the highest SUV peak value was computed automatically.…”
Section: Mpercist and Other Pet-parametersmentioning
confidence: 99%
“…They found 35% of complete response, 6% of partial response, and 59% of disease progression. And the median overall survival was 8.8 months [ 21 ]. However, none of these patients had PACC.…”
Section: Discussionmentioning
confidence: 99%
“…A change in SUVpeak and total lesion glycolysis predicted overall survival (p = 0.039; hazard ratio [HR], 0.24; 95% confidence interval [CI], 0.06-0.93), progression-free survival (p = 0.016; HR, 0.15; 95% CI, 0.03-0.69), and time to intrahepatic progression (p = 0.010; HR, 0.16; 95% CI, 0.04-0.65) [24]. Interestingly, in the same study, summed baseline CT diameter of less than 8 cm for the 2 largest liver metastases predicted time to intrahepatic progression (p = 0.013; HR, 0.21; 95% CI, 0.06-0.72) but did not predict overall or progression-free survival [24]. Overall, the body of evidence supports that a reduction of FDG avidity in early PET (4 weeks) might be useful to predict the further outcome of the patients.…”
Section: Fdg-pet-ctmentioning
confidence: 99%